A dangerous path - Hunter, Erin. (New York : HarperCollins, 2004)
Tigerclaw is back and more dangerous than ever as the new leader of ShadowClan, but he is not the most terrifying enemy Fireheart must face as a new force sweeps through the woods.
Booklist, August 2004.
Horn Book, October 2004.
5.9.
5-8.
840L
U
Keywords: Cats -- Fiction; Dogs -- Fiction; Fantasy; Cats -- Fiction; Dogs -- Fiction; Fantasy fiction; Fantasy